Unprecedented plasmon-induced nitroxide-mediated polymerization (PI-NMP): a method for preparation of functional surfaces; Journal of Materials Chemistry A; Vol. 7, iss. 20 - Guselnikova O. A. Olga Andreevna; Marque Sylvain R. A.; Tretyakov E. Evgeny; Mares D. David; Jerabek V. Vitezslav; Audran G. Gerard; Joly J. -P. Jean-Patrick; Trusova M. E. Marina Evgenievna; Svorcik V. Vaclav; Lyutakov O. Oleksy; Postnikov P. S. Pavel Sergeevich (2019, 2019)
Title screen